Who You Know in Hollywood: A Network Analysis of Television Writers. Issue 1 (2nd January 2016) - Phalen, Patricia F.; Ksiazek, Thomas B.; Garber, Jacob B.
Abstract : "It's who you know, not what you know, " is a familiar phrase—often repeated by professionals in Hollywood. The present study focuses on "who knows who" among Hollywood television writers. Using network analysis, this exploratory study identifies the degree of centralization and types of connections found in this elite writers' network. Results show a great deal of collaboration in the network, and while male writers are more connected overall in Hollywood, women are more likely to be brokers—a structurally advantageous position. The authors provide explanations for collaboration patterns, especially with regard to gender differences in network roles, and propose avenues for further research.